Effect of dental wear, stabilization appliance and anterior tooth reconstruction on mandibular movements during speech - Serrano,Priscila de Oliveira (2008)
This study described changes in mandibular movements during pronunciation of /m/ and /s/ sounds in Portuguese, in patients presenting dental wear before and after appliance insertion and tooth reconstruction. Subjects were divided into a control group of dentate patients and an experimental group of patients with incisal tooth wear due to bruxism. A magnetic jaw tracking device measured the jaw opening, and translations to left and right sides of the mandible during pronunciation of phonemes. Evaluations were carried out 1 week and immediately before appliance insertion; 24 h, 7, 30 and 60 days after appliance insertion; and 1 week and 1 month after tooth reconstruction. Data were submitted to two-way ANOVA, Mann-Whitney and Friedman tests (p<0.05). Jaw opening was different (p<0.05) for both sounds in all periods. The anteroposterior amplitude for /s/ showed differences immediately before and 1 month after appliance insertion (p<0.05). Lateral amplitude for the right side showed differences between groups after appliance insertion for /s/, and 1 and 2 months after appliance insertion for the /m/ (p<0.05). Volunteers with anterior tooth wear had a wider opening movement, and the movements during speech of /m/ and /s/ sounds were not changed after appliance insertion and reconstruction of teeth.